Komunikasi yang Canggih di Era Society Industri 5.0 - Afriyani, Wilda; Harahap, Mickael Halomoan; Harahap, Nursapia (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Industry 5.0 is a new industrial era characterized by the use of advanced technology such as the Internet of Things (IoT), artificial intelligence (AI), and robotics. In this day and age, communication has become increasingly important as technological advances allow humans to interact more effectively with machines and systems. Advanced communications in the Industry 5.0 era require the use of new technologies such as augmented reality (AR) and virtual reality (VR) to enhance the user experience. For example, in manufacturing, AR can be used to visually guide workers through the production process, and VR can be used for training and simulations. In addition, AI technology also enables more effective communication between humans and machines. For example, in the automotive industry, AI can be used to monitor vehicle performance and provide early warning if there is a problem. This reduces downtime and increases production efficiency. As communication technology advances, concerns arise regarding changes in communication ethics. Apart from the many positive benefits, virtual communication also has a negative impact on society. This includes the development of individualistic personalities which can give rise to social communication crises, especially among the younger generation. This article discusses the communication ethics of young women on social media. Basically, communication ethics is very important and easy to implement. Both as media and as media. Good communication ethics prevent misunderstandings and arguments that lead to mutual insults. If the communication is rude, impolite, and far from moral values, especially if it is spread via unknown social media, then it is useless and will not provoke or cause conflict Maybe so